ANALISIS KOMPARASI WORD OF MOUTH, PROMOSI MELALUI INSTAGRAM DAN KEPUTUSAN PEMBELIAN Studi Kasus Toko Kosmetik Pandalovely Dan Ayucitra Cosmetics - Latifah, Fahrul; Pujianto, Agung; Mulyati, Diana Juni (Research Journal of Social Science and Economics, 2025)
The growth trend of the cosmetics market in Indonesia began to grow in 2017 until 2023 it began to increase. So that it can be analyzed because the increase in the cosmetic market shows that Indonesian consumer loyalty is relatively low. Opportunities to switch brands and mutually exchange products tend to be higher than presentations to be loyal to one particular brand. Consumers in Indonesia mostly prefer to experiment with different brands for the same product. The researcher decided to compare the two stores which both sell cosmetics and skincare. In this study researchers used quantitative research methods. The quantitative approach is research based on the philosophy of positivism to examine a certain population or sample and take samples randomly. The data collection technique used in this quantitative research is to distribute questionnaires via google form and have been compiled based on the indicators that have been described. According to Nazir (2005: 58) comparative research is a type of descriptive research that wants to find answers fundamentally about cause and effect, by analyzing the factors that cause the occurrence or emergence of a particular phenomenon. Using the Snowball sampling technique is an approach to finding key informants who have a lot of information. The analysis technique used in this study is the independent t test. In the discussion after doing some statistical tests. Then there are the results of the analysis which prove that the two stores have differences in word of mouth variants, promotions via Instagram and purchasing decisions.